An Evolutionary Analysis of the Volunteer's Dilemma. - Myatt, D; Wallace, C (2008)
A public good is produced if and only if a volunteer provides it. There are many pure-strategy Nash equilibria in each of which a single player volunteers. Noisy strategy revisions (for instance, quantal responses) allow play to evolve. Equilibrium selection is achieved via the characterisation of long-run play as revisions approximate best replies. The volunteer need not be the lowest-cost player: relatively high-cost, but nonetheless "reliable" players may instead produce the public good. More efficient players provide when higher values are associated with lower costs. Voluntary open-source software provision offers a contemporary application.